2023
DOI: 10.3389/fimmu.2023.1114582
|View full text |Cite
|
Sign up to set email alerts
|

The role of AMPK in cancer metabolism and its impact on the immunomodulation of the tumor microenvironment

Abstract: Adenosine monophosphate-activated protein kinase (AMPK) is a key metabolic sensor that is pivotal for the maintenance of cellular energy homeostasis. AMPK contributes to diverse metabolic and physiological effects besides its fundamental role in glucose and lipid metabolism. Aberrancy in AMPK signaling is one of the determining factors which lead to the development of chronic diseases such as obesity, inflammation, diabetes, and cancer. The activation of AMPK and its downstream signaling cascades orchestrate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 182 publications
0
39
0
Order By: Relevance
“…To showcase the potential of SignalingProfiler, we took advantage of our previously published transcriptome, proteome, and phosphoproteome dataset of breast cancer cells upon treatment with metformin (Sacco et al , 2016), whose molecular targets (the mammalian target of rapamycin, mTOR, and the AMP-activated protein kinase, AMPK) and phenotypic impact are well characterized (Keerthana et al , 2023; Garcia & Shaw, 2017; Salminen & Kaarniranta, 2012; Saxton & Sabatini, 2017; Gao et al , 2020; Madsen et al , 2015; Salani et al , 2014) ( Figure 2A ). Here we aim to validate whether SignalingProfiler can unbiasedly and systematically recapitulate from multi-omics data the metformin-induced signaling rewiring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To showcase the potential of SignalingProfiler, we took advantage of our previously published transcriptome, proteome, and phosphoproteome dataset of breast cancer cells upon treatment with metformin (Sacco et al , 2016), whose molecular targets (the mammalian target of rapamycin, mTOR, and the AMP-activated protein kinase, AMPK) and phenotypic impact are well characterized (Keerthana et al , 2023; Garcia & Shaw, 2017; Salminen & Kaarniranta, 2012; Saxton & Sabatini, 2017; Gao et al , 2020; Madsen et al , 2015; Salani et al , 2014) ( Figure 2A ). Here we aim to validate whether SignalingProfiler can unbiasedly and systematically recapitulate from multi-omics data the metformin-induced signaling rewiring.…”
Section: Resultsmentioning
confidence: 99%
“…A list of 74 proteins with their expected activity modulation to metformin treatment ( protein gold standard ) was compiled from three recent papers (Keerthana et al , 2023; Garcia & Shaw, 2017; Salminen & Kaarniranta, 2012; Saxton & Sabatini, 2017) focusing on mTOR and AMPK pathways. Since metformin inhibits mTOR (and activates AMPK), negative and positive targets of mTOR (and AMPK) were set to active and inactive (inactive and active), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Scheme 1 represented the synthesis of new hybrids of Nsubstituted heteroarylidene of thiazolidine-2,4-diones bearing thiazole heterocycle. Initially, commercially available thiazolidine 2,4-dione (1) was reacted with (1-methylcyclohexyl)methanol (2) under standard Mitsunobu reaction condition (DIAD/PPh 3 ) [25] to get N-substituted intermediate (3) [23] which was further treated with commercially available 2-aminothiazole-5-carbaldehyde (4) using catalytical piperidine to prepare corresponding N-substituted arylidenethiazolidine-2,4-dione (5). The coupling of aminothiazole (5) with 4-nitro-3-(trifluoromethyl)benzenesulfonyl chloride (6) was carried out by TEA at room temperature to get targeted hybrid of N-substituted arylidenethiazolidine-2,4-diones with thiazole-benzenesulfonamide (7) in excellent yield (83%).…”
Section: Chemistrymentioning
confidence: 99%
“…Structurally, AMPK is heterotrimeric in nature and consists of three subunits, namely, catalytic α subunit, regulatory β, and γ subunits encoded with distinct genes for activation/deactivation processes [3,4]. Recent studies showed that activated AMPK functioned as metabolic tumor suppressor that inhibited both PI3K/Akt pathway as well as the cell cycle regulatory proteins p21, p27, and p53 leading to inhibition of cell proliferation and cell cycle arrest [5,6]. Consequently, a number of natural products, herbal medicines, and synthetic small molecule heterocycles have been reported as AMPK activators against various cancer cell growths [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] AMPK's role in thwarting tumorigenic trajectories and its suppressive impact on cell growth and protein genesis is well established. [12,13] This narrative spotlight shifts to metformin, a preeminent medication for type 2 diabetes. Exemplifying notable anticancer virtues, metformin's therapeutic principle hinges on AMPK activation, tempering the glycolytic enthusiasm intrinsic to tumor cells.…”
Section: Introductionmentioning
confidence: 99%